2006
DOI: 10.1007/s10832-006-5415-4
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric ceramics and single crystals for ultrasonic medical transducers

Abstract: Complex system ceramics Pb(Sc 1/2 Nb 1/2 )O 3 -Pb (Mg 1/3 Nb 2/3 )O 3 -Pb(Ni 1/2 Nb 1/2 )O 3 -(Pb 0.965 ,Sr 0.035 )(Zr,Ti) O 3 (PSN-PMN-PNN-PSZT abbreviated to PSMNZT) with extremely high dielectric constants, ε T 33 /ε 0 and ε S 33 /ε 0 , have been synthesized by the conventional technique and the dielectric and piezoelectric properties of the ceramics have been investigated for ultrasonic medical transducers. On the other hand, relaxor-PbTiO 3 single crystals (SCs) of xPb(In 1/2 Nb 1/2 )O 3 -yPb(Mg 1/3 Nb 2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…The resulting bandwidths, over 130%, can be used for a variety of applications including sub-harmonic or second harmonic imaging for increased resolution. [338][339][340][341][342][343][344][345] Several companies, including Philips, GE, Siemens, Hitachi, Toshiba, TRS Technologies, Humanscan, Boston Scientific, HC Materials and etc., have been employing relaxor-PT crystals for medical ultrasonic applications. Toshiba was a pioneer in this field, working on the development of single crystals and phased array transducers for medical imaging applications starting in the 1990 s, while the first low frequency phased array transducer was released to the market in November 2004 by Philips and received excellent market acceptance.…”
Section: Medical Ultrasonic Transducersmentioning
confidence: 99%
“…The resulting bandwidths, over 130%, can be used for a variety of applications including sub-harmonic or second harmonic imaging for increased resolution. [338][339][340][341][342][343][344][345] Several companies, including Philips, GE, Siemens, Hitachi, Toshiba, TRS Technologies, Humanscan, Boston Scientific, HC Materials and etc., have been employing relaxor-PT crystals for medical ultrasonic applications. Toshiba was a pioneer in this field, working on the development of single crystals and phased array transducers for medical imaging applications starting in the 1990 s, while the first low frequency phased array transducer was released to the market in November 2004 by Philips and received excellent market acceptance.…”
Section: Medical Ultrasonic Transducersmentioning
confidence: 99%
“…6 The PIN-PMN-PT single crystals were also investigated earlier by Hosono and Yamashita who reported higher phase transition temperatures: T c = 184°C and T R-T = 89°C, and excellent dielectric and piezoelectric properties. 7 Zhang et al 8 reported an investigation on PIN-PMN-PT system using a larger crystal boule of 50 mm in diameter and 100 mm in length. They reported full set material constants measured using resonance method for three different sections from the same crystal boule.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of the transducer is determined based on the dimensions and characteristics of the tissue and the age of the patient to be imaged. 12,69,70 In order to decrease the reflection of acoustic wave at the transducer-body interface, one or two matching layers are employed on the front side of the transducer. To maximize transmission of acoustic energy from transducer to the medium (human body) and broaden the bandwidth, the thickness of matching layers needs to be equal to =4 (where is the wavelength of acoustic wave in the matching layer at the center frequency).…”
Section: Ultrasonic Transducersmentioning
confidence: 99%
“…absorbed into the human body and cause numerous side effects. [10][11][12][13][14] Some of the common lead-poisoning symptoms with various degrees of severity are mentioned in Table 1.…”
Section: Introductionmentioning
confidence: 99%